Glycogen Synthase Kinase 3 Beta (GSK3β) Phosphorylates the RNAase III Enzyme Drosha at S300 and S302 - Tang, Xiaoli (Public Library of Science, 2011)
The canonical microRNA (miRNA) pathway commences with the enzymatic cleavage of the primary gene transcript (pri-miRNA) by the RNAase III enzyme Drosha in the nucleus into shorter pre-miRNA species that are subsequently exported to the cytoplasm for further processing into shorter, mature miRNA molecules. Using a series of reporter constructs, we have previously demonstrated that phosphorylation of Drosha at Ser 300 and 302 was required for its nuclear localization. Here, we identify GSK3β as the culprit kinase. We demonstrate that Drosha is unable to selectively localize to the nucleus in cells deficient in GSK3β. These findings expand the substrate base of GSK3β to include a central component of the miRNA biogenesis pathway.